6 - Irregular Migration and Vulnerability to HIV&AIDS: Some Observations from Zimbabwe: by France Maphosa - Maphosa, France (Africa Development, 2021)
Mobile populations are at very high risk of HIV infection. At the same time, they can be catalysts in its spread. Migration from Matabeleland region in Zimbabwe to South Africa has several features that increase this dual disposition of those involved. These features include the largely irregular nature of migration, its circulatory nature, increasing feminisation as well as the working and living conditions of the migrants in the host country. Irregular migration exposes migrants to various forms of abuse by thugs, those who purport to assist them on the way and law enforcement agents. At the country of destination, undocumented migrants are often employed in precarious forms of jobs which expose them to abuse by employers and other workers. Female irregular migrants are particularly at risk both on transit and at destination. Although they often spend extended periods of time away from home, migrants occasionally return to their spouses or partners at home. This increases the risk of infection for spouses and partners who are often unable to negotiate for safe sex. Using observations from studies conducted in Ward Seven of Matabeleland Province in Zimbabwe, this article discusses some of the factors that expose migrants, particularly irregular migrants, to HIV infection as well making them catalysts in its spread.